Student’s Self Esteem and Cyber-bullying Behavior in Senior High School - Haura, Azzah Tahani; Ardi, Zadrian (Universitas Negeri Padang, 2020)
Cyberbullying behavior is a phenomenon that often happens among social media users, especially students. The behavior of cyberbullying is a continuous attack on victims by using communication media as a platform. One aspect that can influence a person to do cyber bullying is self-esteem. The purpose of this study is to see the relationship between self-esteem and cyberbullying behavior. This study uses descriptive correlational method with a quantitative approach. This study uses a simple random sampling technique by considering sampling using the G*Power application with a total sample are 100 (n = 100). Data analysis using descriptive analysis and correlation test analysis by using product-moment correlation. The findings of this study indicate that self-esteem related to cyberbullying behavior.